Nanometer heat reflection type roof photovoltaic waterproof coating
By adding modified nanocrystalline stone to the roof waterproof coating, the problem of aging of traditional waterproof materials under high temperature and ultraviolet light is solved, and better heat insulation, reflection and weather resistance are achieved, and are suitable for photovoltaic roofing environments.
Patent Information
- Application Number
- CN202411927724.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
The existing roof waterproof materials aging under high temperature and ultraviolet rays, resulting in a degradation of waterproofing performance, especially in photovoltaic roofing environments.
Nanothermal reflection waterproof coating is used. The coating is made of nano-golded microcrystalline, and the natural quartz sand is sintered and modified by nanomixed powders such as lanthanum oxide, calcium oxide, and boron oxide to form nano-golded microcrystalline with good reflective effect, and then fully dispersed and combined in the polyurea system to improve the heat insulation, reflection and weather resistance of the coating.
This coating not only significantly improves heat insulation and reflective performance, but also extends the service life of waterproof coatings in photovoltaic roof environments, reduces the adverse effects of photovoltaic modules on the coatings, and enhances the photovoltaic power generation frequency.
Smart Images

Figure BDA0005209616020000081 
Figure BDA0005209616020000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coatings, and in particular to a nano heat-reflective waterproof coating for roof photovoltaics. Background Art
[0002] At present, most of the roof waterproofing materials on the market are still asphalt-based waterproof coatings or waterproof membranes. Although asphalt-based waterproof materials have a certain waterproof effect and can effectively prevent hydrophobic penetration into the roof in the short term, they do not perform well in terms of heat insulation, high temperature resistance and aging resistance. Especially in the high temperature environment in summer, asphalt-based waterproof materials are prone to increase the temperature inside the building and affect the energy-saving effect of the building. They are also prone to aging and embrittlement under high temperature and ultraviolet radiation, resulting in a decrease in waterproof performance.
[0003] As the country has vigorously developed the photovoltaic industry in recent years, more and more building roofs have begun to install photovoltaic modules. However, when traditional waterproof materials are used on building roofs equipped with photovoltaic modules, their performance defects become more prominent. First, the installation of photovoltaic modules may cause additional mechanical pressure and vibration to the roof and pre-laid waterproof materials, which will accelerate the aging and damage of waterproof materials. At the same time, photovoltaic modules will generate a lot of heat during long-term operation, which may cause serious thermal damage to the waterproof materials underneath, resulting in further reduction of the waterproof performance and thermal insulation effect of the waterproof materials. Therefore, it is of great market significance to provide a waterproof coating suitable for building roofs containing photovoltaic modules. Summary of the invention
[0004] In order to improve the heat insulation effect of the waterproof coating, enhance the heat aging resistance, and make the waterproof coating more suitable for the waterproof construction of photovoltaic roofs, the present application provides a nano heat reflective roof photovoltaic waterproof coating.
[0005] In the first aspect, the present application provides a nano heat reflective waterproof coating that adopts the following technical solution: A nano heat-reflective waterproof coating, which is prepared by mixing component A and component B in a mass ratio of 1:(1-2); Wherein, the A component comprises the following raw materials in parts by weight: 4,4'-dicyclohexylmethanediamine: 35-50 parts; Polyisocyanate: 50-65 parts; Wherein, the B component comprises the following raw materials in parts by weight: Polyaspartic acid: 40-55 parts; Amino chain extender: 10-20 parts; Nanocrystalline stone: 15-20 parts; Titanium dioxide: 5-12 parts; Defoaming and leveling agent: 1.2-2 parts.
[0006] The nano-microcrystalline stone is prepared by fully mixing natural quartz sand, nano-mixed powder and a binder in a mass ratio of (5-6): (3-4): 1, and then sintering at high temperature, grinding and screening; the nano-mixed powder includes lanthanum oxide and calcium oxide, and the nano-mixed powder also includes one or more of boron oxide and magnesium fluoride, and the binder is a polyvinyl alcohol aqueous solution and phosphoric acid mixed in a mass ratio of (9-9.5): (0.5-1).
[0007] By adopting the above technical solution, the natural quartz sand is sintered and modified by using nano-mixed powders such as lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride, and nano-crystals with good reflective effect can be obtained. Then, as the nano-crystals are fully dispersed and combined in the waterproof coating of the polyurea system, the nano-crystals can form a shielding effect in the waterproof coating, which is conducive to making the waterproof coating have good thermal insulation performance, sunlight reflectivity and weather resistance. At the same time, the waterproof coating can also be used for the construction of waterproof coatings on photovoltaic roofs through its own high sunlight reflectivity. Then, while playing a waterproof role, the waterproof coating can reflect sunlight to the photovoltaic modules, which is conducive to enhancing the photovoltaic power generation frequency.
[0008] Optionally, the nano-mixed powder is a mixture of lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride in a mass ratio of (8-10):(7-8):(1-3):1.
[0009] By adopting the above technical solution, the prepared nanocrystals have better reflective effect, which can further improve the improvement effect on the waterproof coating, so that the waterproof coating has higher thermal insulation performance, reflective performance and weather resistance.
[0010] Optionally, the method for preparing the nano-microcrystalline stone comprises the following steps: A1, the natural quartz sand and the nano mixed powder are fully mixed and ball-milled with water to obtain a mixed slurry, and then the mixed slurry is dried, the binder is added, and mixed pellets are obtained by granulation after stirring evenly, and then the mixed pellets are put into a self-sealing plastic bag and aged for not less than 1 day, and then taken out and dried again to obtain a primary material; A2. Heat the raw material to 650-700°C, maintain the temperature and perform calcination and degreasing for 1-2 hours to obtain a rough blank; A3. Slowly heat the rough blank to 1380-1450℃, maintain the temperature and perform vacuum sintering for 3-4h. After sintering, naturally cool it down to room temperature with the furnace. After taking it out, further crush it, add water to ball mill, dry it, and screen it to obtain nano-microcrystalline stone with a particle size of less than 500nm.
[0011] By adopting the above technical solution, the preparation method is simple and convenient, which is conducive to large-scale industrial production.
[0012] Optionally, in the calcination and degreasing in step A2, an inert gas needs to be circulated in advance, and the primary material is fed into the furnace after the furnace is filled with inert gas, and calcined and degreased in an inert atmosphere; in the vacuum sintering and shaping in step A3, the vacuum degree in the furnace needs to be maintained at less than or equal to 15KPa.
[0013] By adopting the above technical solution, the inert gas circulated in the calcination and degreasing process can fully remove the waste gas generated by the binder during the calcination process, and it is also beneficial to stabilize the calcination and degreasing environment in the degreasing furnace and reduce the occurrence of side reactions. In the vacuum sintering and shaping, the vacuum environment can also reduce the occurrence of adverse reactions such as oxidation and nitridation in the product, which is beneficial to and improves the sintering purity and sintering quality of nano-microcrystalline stone.
[0014] Optionally, the nano-microcrystalline stone needs to undergo surface activation treatment before adding, and the surface activation treatment of the nano-microcrystalline stone includes the following steps: First, the nano-microcrystalline stone is immersed in an acidic solution, heated to 55-60° C., and fully stirred for reaction for 5-10 minutes. The nano-microcrystalline stone is cleaned by vacuum filtration until the cleaning liquid is neutral to obtain acid-treated nano-microcrystalline stone. The acid-treated nano-microcrystalline stone is then immersed in a 2% γ-aminopropyltriethoxysilane solution and continuously immersed for 20-30 minutes. After vacuum filtration, the solution is dried to obtain the nano-microcrystalline stone after surface activation treatment.
[0015] By adopting the above technical scheme, the oxide impurities that are not fully melted and combined in the nano-microcrystalline stone can be effectively removed, and at the same time, the bonding strength between the nano-microcrystalline stone and polyurea can be improved, which is beneficial to give full play to the reinforcing and modifying effects of the nano-microcrystalline stone, and is beneficial to further improve the thermal insulation performance, reflective performance and weather resistance of the waterproof coating.
[0016] Optionally, in the component A, the polyisocyanate is one of hexamethylene diisocyanate and isophorone diisocyanate.
[0017] By adopting the above technical scheme, hexamethylene diisocyanate and isophorone diisocyanate are both aliphatic diisocyanates. By adopting the polyurea semi-prepolymer prepared by aliphatic diisocyanates to react with polyaspartic acid ester, not only the curing speed of the polyurea waterproof coating can be appropriately reduced to facilitate the full leveling of the waterproof coating, but also the tensile strength and elongation of the coating film can be improved, which is beneficial to improving the mechanical properties of the coating film.
[0018] Optionally, in the B component, the amino chain extender is one of dimethylthiotoluene diamine or N,N'-dimethyl-p-diphenylamine.
[0019] By adopting the above technical scheme, dimethylthiotoluenediamine and N,N'-dimethylparaphenylamine are both sterically hindered primary amines. Through the characteristics of high steric hindrance, the reaction activity of primary amines and polyisocyanates can be effectively controlled, thereby controlling the curing process of the waterproof coating and extending its curing time, which is beneficial to the full leveling of the waterproof coating and the formation of a uniform and smooth waterproof coating film, which is beneficial to improve the reflectivity of sunlight and enhance the thermal insulation effect.
[0020] Optionally, the titanium dioxide is rutile titanium dioxide, and the defoaming and leveling agent is polyether-modified polydimethylsiloxane.
[0021] By adopting the above technical solution, rutile titanium dioxide has better weather resistance and hiding performance than anatase titanium dioxide. It is not only not easy to turn yellow and powder, but also has high whiteness and excellent glossiness. The combination with nano-microcrystalline stone is conducive to further improving the weather resistance and thermal insulation performance of waterproof coatings. At the same time, the use of polyether-modified polydimethylsiloxane as a defoaming and leveling agent can reduce the surface tension of polyurea system waterproof coatings, which is conducive to the full leveling of waterproof coatings when sprayed on the roof, and then can form a uniform and smooth waterproof coating film, which is conducive to improving the reflectivity of sunlight and enhancing the thermal insulation effect.
[0022] In the second aspect, the nano heat reflective waterproof coating provided by the present application adopts the following technical solution: A method for preparing a nano heat-reflective waterproof coating comprises the following steps: S1. Preparation of component A: heating 4,4'-dicyclohexylmethanediamine to 105-110°C for decompression dehydration, stopping dehydration when the water content is lower than 0.1%, lowering the temperature to 85-88°C, adding polyisocyanate dropwise while maintaining the temperature while stirring, and controlling the addition to be completed within 2 hours. After the addition is completed, continue to maintain the temperature and allow the reaction to stand for 2-3 hours to obtain component A; S2. Prepare component B: fully mix polyaspartic acid ester, amino chain extender and titanium dioxide, heat to 105-120° C. for decompression dehydration, then cool to below 40° C., add defoaming and leveling agent, and fully stir to obtain component B; S3. Preparation of waterproof coating: The prepared component A and component B are stored separately, and the component A and component B are fully mixed in proportion before use to obtain a nano heat reflective waterproof coating.
[0023] By adopting the above technical solution, In the third aspect, the application of a nano heat reflective waterproof coating provided by the present application adopts the following technical solution: The invention discloses an application of a nano heat-reflective waterproof coating, which is applied to the waterproof coating construction of photovoltaic roofs.
[0024] By adopting the above technical solution, the nano heat reflective waterproof coating with nano microcrystalline stone added has good reflection effect and high sunlight reflectance. When applied to the construction of roof waterproof coating containing photovoltaic modules, it can fully reflect sunlight to photovoltaic modules, which is beneficial to enhance photovoltaic power generation efficiency. In addition, the nano heat reflective waterproof coating with nano microcrystalline stone added also has good heat insulation and weather resistance, which is also beneficial to reduce the adverse effects of photovoltaic modules on waterproof coatings and increase the service life of waterproof coatings.
[0025] In summary, the technical solution of the present application has at least one of the following beneficial effects.
[0026] 1. By sintering and modifying natural quartz sand with nano-mixed powders such as lanthanum oxide, calcium oxide, boron oxide, and magnesium fluoride, nano-crystals with good reflective effects can be obtained. Then, as the nano-crystals are fully dispersed and combined in the waterproof coating of the polyurea system, it is beneficial for the waterproof coating to have good thermal insulation performance, sunlight reflectivity, and weather resistance.
[0027] 2. Due to the high sunlight reflectivity of waterproof coatings, waterproof coatings can be used in the construction of waterproof coatings on photovoltaic roofs. While playing a waterproof role, the waterproof coating can reflect sunlight onto photovoltaic modules, which is beneficial to enhancing the frequency of photovoltaic power generation. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0029] The polyaspartic acid ester is specifically prepared by Michael addition reaction of diethyl maleate and polyetheramine, and the specific grade of the polyetheramine is Jeffamine D230.
[0030] The titanium dioxide was specifically purchased from Pangang Group Co., Ltd., and the grade was R-248 rutile titanium dioxide.
[0031] The defoaming and leveling agent is specifically purchased from BYK Chemicals, with the brand name BKY-331.
[0032] Preparation Example [Preparation Example 1] A nano-microcrystalline stone comprises the following raw materials: 18 kg of natural quartz sand, 9 kg of nano-mixed powder and 3 kg of binder.
[0033] The nano-mixed powder is specifically a mixture of lanthanum oxide, calcium oxide and boron oxide in a mass ratio of 10:8:2, that is, the nano-mixed powder includes 4.5 kg of lanthanum oxide, 3.6 kg of calcium oxide and 0.9 kg of boron oxide. The binder is specifically a mixture of polyvinyl alcohol aqueous solution and phosphoric acid in a mass ratio of 9.5:0.5, that is, the binder specifically includes 2.85 kg of polyvinyl alcohol aqueous solution and 0.15 kg of phosphoric acid. Specifically, in this preparation example, the concentration of the polyvinyl alcohol aqueous solution is 5%.
[0034] A nano-microcrystalline stone is prepared by the following preparation method: A1. Natural quartz sand and nano mixed powder are fully mixed and ball-milled with water to obtain a mixed slurry. The mixed slurry is dried, and then a binder is added. After stirring evenly, mixed pellets are obtained by granulation. The mixed pellets are then put into a self-sealing plastic bag and aged for 1 day. After being taken out, they are dried again to obtain a primary material.
[0035] A2. The raw material is sent into a degreasing furnace, heated to 650°C, maintained at the temperature and calcined and degreased for 2 hours, and then taken out to obtain a rough blank. The degreasing furnace is circulated with nitrogen at a flow rate of 70L / min. After the degreasing furnace is filled with nitrogen, the raw material is sent into the degreasing furnace and calcined and degreased in a nitrogen atmosphere.
[0036] A3. The rough blank is sent into a vacuum sintering furnace and slowly heated to 1420℃ within 3 hours. The temperature is maintained and vacuum sintered for 3 hours. After sintering, the rough blank is naturally cooled to room temperature. After being taken out, it is further crushed, ball-milled with water, dried, and sieved to obtain nano-microcrystalline stone with a particle size of less than 500nm. The vacuum sintering furnace needs to maintain a vacuum degree of less than or equal to 15KPa.
[0037] In the water-adding ball milling process of step A1 and step A3, the mass ratio of the material to the ball milling balls is 1:2:1.
[0038] [Preparation Example 2] A nano-microcrystalline stone comprises the following raw materials: 22.5 kg of natural quartz sand, 7 kg of nano-mixed powder and 3 kg of binder.
[0039] The nano-mixed powder is specifically a mixture of lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride in a mass ratio of 8:8:3:1, that is, the nano-mixed powder includes 3.6 kg of lanthanum oxide, 3.6 kg of calcium oxide, 1.35 kg of boron oxide and 0.45 kg of magnesium fluoride. The binder is specifically a mixture of polyvinyl alcohol aqueous solution and phosphoric acid in a mass ratio of 9:1, that is, the binder specifically includes 2.7 kg of polyvinyl alcohol aqueous solution and 0.3 kg of phosphoric acid. Specifically, in this preparation example, the concentration of the polyvinyl alcohol aqueous solution is 5%.
[0040] A nano-microcrystalline stone is prepared by the following preparation method: A1, natural quartz sand and nano mixed powder are fully mixed and ball-milled with water to obtain a mixed slurry after ball milling, the mixed slurry is dried, and then a binder is added, and mixed pellets are obtained by granulation after stirring evenly, and then the mixed pellets are put into a self-sealing plastic bag and aged for 1 day, and then taken out and dried again to obtain a primary material; A2. The raw material is sent into a degreasing furnace, heated to 700°C, maintained at the temperature and calcined and degreased for 1 hour, and then taken out to obtain a rough blank. The degreasing furnace is circulated with nitrogen at a flow rate of 95L / min. After the degreasing furnace is filled with nitrogen, the raw material is sent into the degreasing furnace and calcined and degreased in a nitrogen atmosphere.
[0041] A3. The rough blank is sent into a vacuum sintering furnace and slowly heated to 1380℃ within 3 hours. The temperature is maintained and vacuum sintered for 4 hours. After sintering, the rough blank is naturally cooled to room temperature. After being taken out, it is further crushed, ball-milled with water, dried, and sieved to obtain nano-microcrystalline stone with a particle size of less than 500nm. The vacuum sintering furnace needs to maintain a vacuum degree of less than or equal to 15KPa.
[0042] In the water-adding ball milling process of step A1 and step A3, the mass ratio of the material, the ball milling balls and the water is 1:2:1.
[0043] [Preparation Example 3] A nano-microcrystalline stone, which is different from [Preparation Example 1] in that the nano-mixed powder is different.
[0044] In this preparation example, the nano-mixed powder is specifically lanthanum oxide, calcium oxide and magnesium fluoride, and the mass ratio of lanthanum oxide, calcium oxide and magnesium fluoride is 10:8:2, that is, the nano-mixed powder includes 4.5 kg of lanthanum oxide, 4.05 kg of calcium oxide and 0.45 kg of magnesium fluoride.
[0045] [Preparation Example 4] A nano-microcrystalline stone, which is different from [Preparation Example 1] in that the nano-mixed powder is different.
[0046] In this preparation example, the nano-mixed powder is specifically lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride in a mass ratio of 10:9:1:1, that is, the nano-mixed powder includes 4.5 kg of lanthanum oxide, 4.05 kg of calcium oxide, 3.6 kg of boron oxide and 0.45 kg of magnesium fluoride.
[0047] [Preparation Example 5] A nano-microcrystalline stone, which is different from [Preparation Example 1] in that the nano-mixed powder is different.
[0048] In this preparation example, the nano-mixed powder is specifically lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride, and the mass ratio of lanthanum oxide, calcium oxide and magnesium fluoride is 10:8:2:1, that is, the nano-mixed powder includes 4.5kg lanthanum oxide, 3.15kg calcium oxide, 0.9kg boron oxide and 0.45kg magnesium fluoride. Example
[0049] [Example 1] A nano heat-reflective waterproof coating comprises an A component and a B component.
[0050] Component A includes 35 kg 4,4'-dicyclohexylmethanediamine and 50 kg hexamethylene diisocyanate, and component B includes 40 kg polyaspartic acid ester, 20 kg amino chain extender, 20 kg nano-microcrystalline stone, 5 kg titanium dioxide and 1.2 kg defoaming and leveling agent.
[0051] Specifically, in component B, the amino chain extender is dimethylthiotoluene diamine, and the nano-microcrystalline stone is specifically a nano-microcrystalline stone prepared in [Preparation Example 1].
[0052] A method for preparing a nano heat-reflective waterproof coating comprises the following steps: S1. Preparation of component A: 4,4'-dicyclohexylmethanediamine was heated to 110°C for decompression dehydration. The dehydration was stopped when the water content was lower than 0.1%. The temperature was lowered to 85°C. Hexamethylene diisocyanate was added dropwise while maintaining the temperature and stirring. The addition was completed within 2 hours. After the addition was completed, the temperature was maintained and the reaction was allowed to stand for 2 hours to obtain component A. S2, preparing component B: fully mixing polyaspartic acid ester, amino chain extender and titanium dioxide, heating to 110° C. for decompression dehydration, then cooling to 40° C., adding defoaming and leveling agent, and fully stirring to obtain component B; S3. Preparation of waterproof coating: The prepared component A and component B are stored separately, and before use, component A and component B are fully mixed in a mass ratio of 1:1 to obtain a nano heat reflective waterproof coating.
[0053] The invention discloses an application of a nano heat-reflective waterproof coating, which is applied to the waterproof coating construction of photovoltaic roofs.
[0054] [Example 2] A nano heat-reflective waterproof coating comprises an A component and a B component.
[0055] Component A includes 40 kg 4,4'-dicyclohexylmethanediamine and 65 kg isophorone diisocyanate, and component B includes 55 kg polyaspartic acid ester, 10 kg amino chain extender, 15 kg nano-microcrystalline stone, 12 kg titanium dioxide and 2 kg defoaming and leveling agent.
[0056] Specifically, in component B, the amino chain extender is N,N'-dimethyl-p-diphenylamine, and the nano-microcrystalline stone is specifically a nano-microcrystalline stone prepared in [Preparation Example 2].
[0057] A method for preparing a nano heat-reflective waterproof coating comprises the following steps: S1. Preparation of component A: heating 4,4'-dicyclohexylmethanediamine to 105°C for decompression dehydration, stopping the dehydration when the water content is lower than 0.1%, lowering the temperature to 88°C, adding isophorone diisocyanate dropwise while maintaining the temperature and stirring, and controlling the addition to be completed within 2 hours. After the addition is completed, continue to maintain the temperature and allow the reaction to stand for 3 hours to obtain component A; S2, preparing component B: fully mixing polyaspartic acid ester, amino chain extender and titanium dioxide, heating to 105° C. for decompression dehydration, then cooling to 40° C., adding defoaming and leveling agent, and fully stirring to obtain component B; S3. Preparation of waterproof coating: The prepared component A and component B are stored separately, and before use, component A and component B are fully mixed in a mass ratio of 1:2 to obtain a nano heat reflective waterproof coating.
[0058] The invention discloses an application of a nano heat-reflective waterproof coating, which is applied to the waterproof coating construction of photovoltaic roofs.
[0059] [Example 3] A nano heat-reflective waterproof coating, which differs from [Example 1] in that the nano microcrystalline stone is different.
[0060] In this embodiment, the nano-microcrystalline stone is specifically selected from the nano-microcrystalline stone prepared in [Preparation Example 3].
[0061] [Example 4] A nano heat-reflective waterproof coating, which differs from [Example 1] in that the nano microcrystalline stone is different.
[0062] In this embodiment, the nano-microcrystalline stone is specifically selected from the nano-microcrystalline stone prepared in [Preparation Example 4].
[0063] [Example 5] A nano heat-reflective waterproof coating, which differs from [Example 1] in that the nano microcrystalline stone is different.
[0064] In this embodiment, the nano-microcrystalline stone is specifically selected from the nano-microcrystalline stone prepared in [Preparation Example 5].
[0065] [Example 6] A nano heat reflective waterproof coating, which is different from [Example 5] in that the nano microcrystalline stone is subjected to surface activation treatment before mixing. The surface activation treatment of the nano microcrystalline stone includes the following steps: First, the nano-microcrystalline stone is immersed in an acidic solution, heated to 55°C, and fully stirred for reaction for 10 minutes. The nano-microcrystalline stone is cleaned by vacuum filtration until the cleaning liquid is neutral to obtain acid-treated nano-microcrystalline stone. The acid-treated nano-microcrystalline stone is then immersed in a 2% γ-aminopropyltriethoxysilane solution and soaked for 30 minutes. After vacuum filtration and drying, the nano-microcrystalline stone with surface activation treatment is obtained.
[0066] Comparative Example [Comparative Example 1] A waterproof coating, which differs from [Example 1] in that nano-microcrystalline stone is not added.
[0067] In this comparative example, the nano-crystalline stone is replaced by an equal amount of natural quartz sand with a particle size less than 500 nm.
[0068] Performance Testing 1. Thermal insulation test: Test according to Appendix B of GB / T 25261-2018 Reflective thermal insulation coating for building, and record the thermal insulation temperature difference ΔT between the waterproof coating prepared in each embodiment and comparative example and the reference blackboard. The test sample and the reference blackboard are also prepared according to Section 3 of Appendix B of GB / T 25261-2018 Reflective thermal insulation coating for building.
[0069] 2. Solar reflectance: Refer to Section 6.4 of GB / T 25261-2018 Reflective Thermal Insulation Coatings for Buildings for testing, and record the solar reflectance of the waterproof coatings prepared in each embodiment and comparative example.
[0070] 1. Aging resistance test: First, prepare the coating film according to Section 4 of "GB / T 16777-2008 Test Method for Building Waterproof Coatings", and fully maintain it according to Table 1. Then refer to Section 9.2.6 of "GB / T 16777-2008 Test Method for Building Waterproof Coatings" for testing, and calculate and record the tensile property retention rate (%) of each embodiment and comparative example before and after artificial weathering aging.
[0071] Table 1 Partial performance test data of waterproof coating Combining Example 1 with Comparative Example 1 and the data in Table 1, it can be seen that under the same polyurea waterproof coating system, Example 1 forms nano-microcrystalline stone by sintering and modifying natural quartz sand with lanthanum oxide, calcium oxide, and boron oxide. Compared with the natural quartz sand added in Comparative Example 1, it can effectively improve the thermal insulation performance and sunlight reflectivity of the polyurea waterproof coating, and also improve the weather resistance of the waterproof coating. This may be because after sintering and modifying natural quartz sand with lanthanum oxide, calcium oxide, and boron oxide, the crystal phase content of the nano-microcrystalline stone is increased, so that the nano-microcrystalline stone has a good reflective effect, and then as the nano-microcrystalline stone is fully dispersed and combined in the coating, the nano-microcrystalline stone can form a shielding effect in the coating, thereby achieving the purpose of reflecting sunlight and resisting thermal aging, and at the same time, it can also reduce the thermal conductivity of the waterproof coating and improve the thermal insulation effect of the waterproof coating.
[0072] Combining the data of Example 1 with Examples 3-5 and Table 1, it can be seen that when the nano-mixed powder in the nano-microcrystalline stone is lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride mixed in a certain proportion, the improvement effect of the nano-microcrystalline stone on the waterproof coating can be further improved.
[0073] Combining the data of Example 5 and Example 6 and Table 1, it can be seen that the improvement effect of the nano-microcrystalline stone on the waterproof coating can be further improved by surface activation treatment of the nano-microcrystalline stone, so that the waterproof coating has better thermal insulation performance, reflective performance and weather resistance. This may be because after the nano-microcrystalline stone is acid-treated and aminosilane-modified, it can not only remove the oxide impurities that are not fully melt-bonded in the nano-microcrystalline stone, but also improve the bonding strength between the nano-microcrystalline stone and the polyurea, which is conducive to giving full play to the enhancement and modification effect of the nano-microcrystalline stone, and further improving the thermal insulation performance, reflective performance and weather resistance of the polyurea waterproof coating.
[0074] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A nano heat reflective waterproof coating, characterized in that: It is prepared by mixing component A and component B in a mass ratio of 1:(1-2); Wherein, the A component comprises the following raw materials in parts by weight: 4,4'-dicyclohexylmethanediamine: 35-50 parts; Polyisocyanate: 50-65 parts; Wherein, the B component comprises the following raw materials in parts by weight: Polyaspartic acid: 40-55 parts; Amino chain extender: 10-20 parts; Nanocrystalline stone: 15-20 parts; Titanium dioxide: 5-12 parts; Defoaming and leveling agent: 1.2-2 parts; The nano-microcrystalline stone is prepared by mixing natural quartz sand, nano-mixed powder and a binder in a mass ratio of (5-6): (3-4): 1, and then sintering, grinding and screening. The nano-mixed powder includes lanthanum oxide and calcium oxide, and the nano-mixed powder also includes one or more of boron oxide and magnesium fluoride. The binder is a polyvinyl alcohol aqueous solution and phosphoric acid mixed in a mass ratio of (9-9.5): (0.5-1).
2. The nano heat reflective waterproof coating according to claim 1, characterized in that: The nano-mixed powder is lanthanum oxide, calcium oxide, boron oxide and magnesium fluoride mixed in a mass ratio of (8-10): (7-8): (1-3):
1.
3. The nano heat reflective waterproof coating according to claim 2, characterized in that: The preparation method of the nano-microcrystalline stone comprises the following steps: A1, the natural quartz sand and the nano mixed powder are fully mixed and ball-milled with water to obtain a mixed slurry, and then the mixed slurry is dried, the binder is added, and mixed pellets are obtained by granulation after stirring evenly, and then the mixed pellets are put into a self-sealing plastic bag and aged for not less than 1 day, and then taken out and dried again to obtain a primary material; A2. Heat the raw material to 650-700°C, maintain the temperature and perform calcination and degreasing for 1-2 hours to obtain a rough blank; A3. Slowly heat the rough blank to 1380-1450℃, maintain the temperature and perform vacuum sintering for 3-4h. After sintering, naturally cool it down to room temperature. After taking it out, further crush it, add water to ball mill, dry it, and screen it to obtain nano-microcrystalline stone with a particle size of less than 500nm.
4. The nano heat reflective waterproof coating according to claim 3, characterized in that: In the calcination and degreasing of step A2, inert gas needs to be circulated in advance, and the primary material is fed into the furnace after the furnace is filled with inert gas, and calcination and degreasing are carried out in an inert atmosphere; in the vacuum sintering and shaping of step A3, the vacuum degree in the furnace needs to be maintained at less than or equal to 15KPa.
5. The nano heat reflective waterproof coating according to claim 2, characterized in that: The nano-microcrystalline stone needs to be surface activated before adding, and the surface activation of the nano-microcrystalline stone includes the following steps: First, the nano-microcrystalline stone is immersed in an acidic solution, heated to 55-60° C., and fully stirred for reaction for 5-10 minutes. The nano-microcrystalline stone is cleaned by vacuum filtration until the cleaning liquid is neutral to obtain acid-treated nano-microcrystalline stone. The acid-treated nano-microcrystalline stone is then immersed in a 2% γ-aminopropyltriethoxysilane solution and continuously immersed for 20-30 minutes. After vacuum filtration, the solution is dried to obtain the nano-microcrystalline stone after surface activation treatment.
6. The nano heat reflective waterproof coating according to claim 1, characterized in that: In the component A, the polyisocyanate is one of hexamethylene diisocyanate and isophorone diisocyanate.
7. The nano heat reflective waterproof coating according to claim 1, characterized in that: In the B component, the amino chain extender is one of dimethylthiotoluenediamine and N,N'-dimethyl-p-diphenylamine.
8. The nano heat reflective waterproof coating according to claim 1, characterized in that: The titanium dioxide is rutile titanium dioxide, and the defoaming and leveling agent is polyether-modified polydimethylsiloxane.
9. A method for preparing a nano heat reflective waterproof coating, used for preparing a nano heat reflective waterproof coating as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of component A: heating 4,4'-dicyclohexylmethanediamine to 105-110°C for decompression dehydration, stopping dehydration when the water content is lower than 0.1%, lowering the temperature to 85-88°C, adding polyisocyanate dropwise while maintaining the temperature and stirring, and controlling the addition to be completed within 2 hours. After the addition is completed, continue to maintain the temperature and allow the reaction to stand for 2-3 hours to obtain component A; S2. Prepare component B: fully mix polyaspartic acid ester, amino chain extender and titanium dioxide, heat to 105-120° C. for decompression dehydration, then cool to below 40° C., add defoaming and leveling agent, and fully stir to obtain component B; S3. Preparation of waterproof coating: The prepared component A and component B are stored separately, and the component A and component B are fully mixed in proportion before use to obtain a nano heat reflective waterproof coating.
10. An application of a nano heat reflective waterproof coating, applicable to a nano heat reflective waterproof coating as claimed in any one of claims 1 to 8, characterized in that: Used in the construction of waterproof coating on photovoltaic roofs.
Citation Information
Patent Citations
Formulation of imperforate micro-spar sheet material and manufacturing method thereof
CN101265027A
Method for preparing sintering black glass ceramics by using red mud to assist calcium, iron and silicon slag
CN107010840A
Reflective insulation building coating
CN107418263A
Waterproof coating, preparation method thereof and waterproof system containing same as well as construction method
CN108034347A
Wollastonite obtd by sintering calcium and silica cpds - with unreactive promoters like borax to reduce reaction temps
FR2239423A1